1998
DOI: 10.1177/03635465980260041401
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Platelet-Derived Growth Factor-BB on Healing of the Rabbit Medial Collateral Ligament

Abstract: We report a biologic approach to improve medial collateral ligament healing using growth factors normally expressed in healing tissue. Our previous in vitro work demonstrated that platelet-derived growth factor-BB and transforming growth factor-beta 1 promoted fibroblast proliferation and matrix synthesis, respectively. There-fore, these growth factors were used in vivo to determine whether they could improve medial collateral ligament healing, whether this effect was dose-dependent, and if combinations of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
3
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(164 citation statements)
references
References 25 publications
3
154
3
4
Order By: Relevance
“…The highest dose in our study was three times less than the dose previously reported in studies investigating the effects of PDGF-BB on soft tissue healing [16,20]. A recent study investigating growth factor expression profile after rotator cuff surgery in a rabbit model noted that PDGF-BB expression was most prominent during Days 7 through 14 postsurgery [18].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The highest dose in our study was three times less than the dose previously reported in studies investigating the effects of PDGF-BB on soft tissue healing [16,20]. A recent study investigating growth factor expression profile after rotator cuff surgery in a rabbit model noted that PDGF-BB expression was most prominent during Days 7 through 14 postsurgery [18].…”
Section: Discussioncontrasting
confidence: 54%
“…After medial collateral ligament rupture in rabbits, 20 lg of PDGF-BB with fibrin sealant delivered on the ligamentous surface demonstrated greater cellularity and vascularity, increased cross-sectional area, and greater ultimate load and energy absorbed to failure at 6 weeks postsurgery compared with the fibrin sealant group [16]. In a rat patellar tendon-defect model, a single bolus injection of 1 lg PDGF into the wound site led to greater cellular proliferation at 2 weeks for early supplementation and increased peak load, cross-sectional area, and pyridinoline content for later supplementation [5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…From a biomechanics perspective, rabbit medial collateral ligament scars fail at measures between 30 and 50% of normal values. [2][3][4] Even at subfailure, or low loads, scar has more creep (stretches out more) than normal ligament. 5 Biochemically, water content, collagen amounts and types, and other matrix components are altered.…”
Section: Clinical Problemsmentioning
confidence: 99%
“…This is an additional limitation of this study. Regarding PDGF from main platelet alpha-granule content, Hildebrand et al (1998) reported that the application of PDGF significantly enhanced healing of the medial collateral ligament injury in a rabbit model. Recently, however, Nagumo et al (2005) reported that PDGF has no effect on the mechanical deterioration of in situ frozen ACL.…”
Section: Discussionmentioning
confidence: 99%